Risk of multiple sclerosis after optic neuritis in patients with normal baseline brain MRI - Marques, IB (2014)
When assessing and managing a patient with optic neuritis (ON), the risk of future development of multiple sclerosis (MS) is an important issue, as this can be the first presentation of the disease. Although the presence of lesions on baseline brain MRI is the strongest predictor of MS conversion, some patients with normal imaging also develop MS. We aimed to estimate MS risk in patients with ON and a normal baseline MRI and identify individuals with higher risk of conversion. We performed a retrospective study including patients with idiopathic ON and normal baseline brain MRI who presented to our hospital over an 8year period. Of a total of 42 patients, 10 converted to MS: five during the first follow-up year, seven during the first 2years and all of the patients within the first 5years, with a 5year MS conversion rate of 23.8%. MS conversion rates were significantly higher in patients with history of previous symptoms suggestive of demyelination (p=0.002), cerebrospinal fluid oligoclonal bands unmatched in serum (p=0.004) and incomplete visual acuity recovery (⩽6/12) after 1year (p=0.002). Lower conversion rates were found in patients with optic disc edema (p=0.022). According to these results, a significant proportion of patients with idiopathic ON and a normal baseline brain MRI will develop MS, with a higher risk during the first 5years. Therefore, in the presence of factors in favor of MS conversion, close follow-up, including semestral medical consultations and yearly brain MRI, can be recommended. Early immunomodulatory treatment may be individually considered as it can delay conversion and reduce new lesion development rate.